LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING UNTUK MENINGKATKAN PERILAKU BERORGANISASI SISWA KELAS VIIIE SMPN 3 SELONG - yulianti, dewi; Marfu’atun, Marfu’atun; Husnussifak, Siti (JKP (Jurnal Konseling Pendidikan), 2024)
In this research, a quantitative approach was used, and the method employed was experimental, with a one-group pre-test and post-test design. The population for this study consisted of 8th-grade students, and the sample size was 10 students. Data collection techniques included observation, interviews, and questionnaires. The aim of this research was to determine the improvement in students' organizational behavior through group guidance services using role-playing techniques. Based on the data analysis using a t-test, the results showed that the t-value was greater than the t-table value (4.64 > 2.262) at a 5% significance level. This indicates that there is an influence of group guidance services using role-playing techniques in enhancing organizational behavior among 8th-grade students at SMPN 3 Selong. Thus, Ha (the research hypothesis) is accepted, while Ho (the null hypothesis) is rejected. In conclusion, there is a significant impact of group guidance services using role-playing techniques in improving organizational behavior among 8th-grade students at SMPN 3 Selong.